Novel light therapies in treatment of onychomycosis - Erkiert-Polguj, Anna; Algiert, Barbara; Rotsztejn, Helena (Dermatology Review/Przegląd Dermatologiczny, 2016)
Onychomycosis is a frequent nail disease. Standard treatment is not sufficient in some patients. The aim of the study is to provide an overview of laser, UVC and photodynamic therapy of onychomycosis. The use of Nd:YAG laser is described in many articles, and also diode lasers and ablative CO2 are used. Some authors, in order to improve the efficiency of treatment, also administered topical antifungal therapy or removed a part of the nail. Also photodynamic therapy usually used in precancerous diseases or superficial skin tumors is also employed in onychomycosis with the same or new photosensitizers. The results and the lack of serious side effects encourage the use of these methods, although none has been compared to standard oral therapy.